2022
DOI: 10.1093/femsle/fnac102
|View full text |Cite
|
Sign up to set email alerts
|

Introducing multiple-gene mutations in Pleurotus ostreatus using a polycistronic tRNA and CRISPR guide RNA strategy

Abstract: The white-rot fungus Pleurotus ostreatus is an agaricomycete that is frequently used in molecular genetics studies as many useful tools are applicable to the fungus. In particular, efficient gene targeting using homologous recombination and CRISPR/Cas9 enables the introduction of a mutation in the gene of interest for functional analysis. Multiple genes encoding various lignocellulose-degrading enzymes are predicted to be present in the genome; therefore, analyses of multiple-gene mutants are required to eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The resulting plasmids were named pCcPef3‐126‐ vp2 , pCcPef3‐126‐ vp3 , pCcPef3‐126‐ mnp3 , and pCcPef3‐126‐ mnp6 , respectively. It was confirmed that a mutation in each mnp / vp was frequently (75%–100%) introduced into the hygromycin B‐resistant strains transformed with each plasmid (Xu et al, 2022; data not shown).…”
Section: Methodsmentioning
confidence: 77%
See 4 more Smart Citations
“…The resulting plasmids were named pCcPef3‐126‐ vp2 , pCcPef3‐126‐ vp3 , pCcPef3‐126‐ mnp3 , and pCcPef3‐126‐ mnp6 , respectively. It was confirmed that a mutation in each mnp / vp was frequently (75%–100%) introduced into the hygromycin B‐resistant strains transformed with each plasmid (Xu et al, 2022; data not shown).…”
Section: Methodsmentioning
confidence: 77%
“…The sgRNA insertion into the plasmids was verified using Sanger sequencing. The resulting plasmids were named respectively. It was confirmed that a mutation in each mnp/vp was frequently (75%-100%) introduced into the hygromycin B-resistant strains transformed with each plasmid (Xu et al, 2022;data not shown).…”
Section: Plasmid Constructionmentioning
confidence: 73%
See 3 more Smart Citations